IMPLEMENTASI PERATURAN DAERAH KABUPATEN SIAK NOMOR 37 TAHUN 2002 TENTANG KETERTIBAN UMUM (STUDI PENGGUNAAN BADAN JALAN DI KECAMATAN SABAK AUH KABUPATEN SIAK TAHUN 2019) - Agung Budiono; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
One of the organizers of public order and public order is the Civil Service Police Unit, abbreviated as Satpol PP. The task of Satpol PP in PP RI No. 16/2018 Regarding Satpol PP Article 4 has the task of enforcing Regional Regulations and organizing public order and public order and protection of the community. In Siak Regency Regional Regulation No. 37/2002 on Public Order Article 16 prohibits street vendors from selling on roads, parks, green lanes and public places. However, the facts in the field are that there are still many people who place objects or goods on the edge or side of public roads, whether for trading purposes or not for trading purposes, there is no control from the authorities (Satpol PP). The formulation of this research is how the Satpol PP implement the Siak Regency Regional Regulation No. 37/2002 on Public Order (Study of the Use of Road Bodies in Sabak Auh District, Siak Regency, 2019)? The purpose of this research is to analyze and describe the Satpol PP in implementing the Siak Regency regional regulation number 37/2002 concerning Public Order (Study on Utilization of Road Bodies in Sabak Auh District, Siak Regency, 2019). This research is a descriptive research type. Data collection techniques in this study used interviews, field observations and documentation. The data analysis technique uses the interactive model qualitative data analysis method. The findings that can be concluded are the implementation of the Siak Regency Regional Regulation Number 37 of 2002 concerning Public Order which is carried out by Satpol PP is considered to be less than optimal, this is based on the findings of research in the field, namely; 1) The community ignores these regional regulations even though Sapol PP has appealed to a ban on selling on the road, lacking Satpol PP personnel. 2) There are people who complain about the existence of street vendors who have the potential to cause congestion, there has been no change from the target recipient of the policy. 3) The types of social and environmental benefits, as well as the degree of change targeted by the regional regulation, have not been maximally felt by the community. 4) The strategy has no significant impact and the Satpol PP's lack of commitment in implementing the regional regulation. Keywords: Policy Implementation, Street Vendors, Satpol PP, Merille S. Grindle Model Policy Implementation.